The Attention Network Test Database: ADHD and Cross-Cultural Applications - Arora, Swasti; Lawrence, Michael A.; Klein, Raymond M. (Frontiers in Psychology, 2020)
Attention is a central component of cognitive and behavioural processes and plays a key role in basic and higher-level functioning. Posner’s model of attention describes three components or networks of attention: the alerting, which involves high intensity states of arousal; the orienting, which involves the selective direction of attention; and the executive control, which involves cognitive functions such as conflict resolution and working memory. The Attention Network Test (ANT) is a computerized testing measure that was developed to measure these three networks of attention. This project describes the ANT, its widely used variants, and the recently developed ANT Database, a repository of data extracted from all studies that have used the ANT as of 2019. To illustrate the potential uses of the database, two meta-analyses conducted using the ANT Database are described. One explores task performance in children with and without ADHD. The other one explores regional differences between studies conducted in China, Europe, and the United States. We are currently in the process of integrating the database into a publicly available web interface. When that work is complete, researchers, clinicians and the general public will be able to use the database to explore topics of interest related to attention.